Soil Organic Carbon Store in Different Forests of India - Jha, M. N.; Gupta, M. K.; Saxena, Alok; Kumar, Rajesh (Indian Forester, 2003)
Global warming and emission of CO2 are of world wide concern because these are creating environmental imbalance and are a long term threat to the well being of all life on earth. Soil is a major sink of carbon. 9815.95 million tonnes of Soil Organic Carbon (SOC) store was estimated in total forest soils (as per 1994 forest stands) under 19 species spread over 27 States and Union territories in India. Spruce forest soil has maximum SOC store (386.0 t/ha) while Khair has minimum (51.93 t/ha). In India , miscellaneous forests are spread over an area of 40.7316 million ha , and their soils have maximum SOC store (6469.80 million tonnes) while in Hollong forest with an area of 0.0068 million ha , soils have the least SOC store (0.82 million million tonnes). Among the Indian States , Arunachal Pradesh has maximum SOC store (1702.08 million tonnes) while Dadra&Nagar Haveli has minimum (2.42 million tonnes) SOC store. Arunachal Pradesh ranks first in India having 248.11 t/ha SOC store in the soils of the State. Soil conservation practices should be strengthened to conserve these natural resources so that carbon store may not deplete especially from hilly terrain.